PMO-192 A retrospective comparison of the performance of Olympus Q series colonoscopes and Pentax HiLine at screening colonoscopy. (28th May 2012) - Chernolesskiy, A; Swain, D; Lee, J; Corbett, G; Cameron, E A B
Abstract : Introduction: There is a small rate of interval cancer after colonoscopy partly due to incomplete lesion detection during the procedure. Some studies have shown superior lesion detection with improved endoscopic image quality and enhancement 1 2 with one suggesting a 50% increase in polyp detection with Pentax HiLine (PH) over Olympus Lucera series (OL) colonoscopes. We have compared the performance of these two systems. Methods: All complete bowel cancer screening colonoscopies performed by a single endoscopist between 18 March 2010 and 27 September 2011 in faecal occult blood test positive patients (n=483) were analysed for insertion/withdrawal time, patient comfort/sedation doses and lesion detection (total polyps, adenomas, advanced, right sided). Comparisons were made between OL (white light) and PH (white light high definition on insertion, i-scan 1 on withdrawal). Differences between groups were analysed using either the Mann–Whitney U test or χ 2 test. Results: Completion rates were similar (OL 413/425; 97.2% and PH 55/58; 94.9%, p=0.24). The two groups were matched for age and sex. Adenoma detection rates were comparable (49% vs 56%, p=0.38). There was no significant difference in terms of mean insertion time, withdrawal time in normal colonoscopies, total numbers of polyps, adenomas, proximal adenomas or advanced adenomas (>1 cm, villous, with high grade dysplasia or containing cancer). The sample size gave an 88% power to detect the higher polyp detection rate detected previously. 2 There was a small statistically significant increase in nurse reported patient discomfort with PH (0.5 vs 1, p<0.0001—none=0, minimal=1, mild=2, moderate=3, severe=4) with higher requirements for Midazolam and similar Fentanyl doses. Conclusion: In this uncontrolled single endoscopist series in a homogenous group of patients, there did not appear to be a significant benefit of one system over the other in terms of procedure duration or lesion recognition. PH colonoscopes did appear to lead to a slight increase in patient discomfort and sedation requirements. A randomised controlled trial is required to establish the relative performances of these systems. Competing interests: None declared. References: 1. Hoffman A, et al. Endoscopy 2010;42 :827–33. 2. Banks, et al. World J Gastroenterol 2011;17 :4308–13.